Kajian Repurposing Drug sebagai Prioritas Metode Pengembangan Obat - Rosa Adelina (UIN Syarif Hidayatullah Jakarta, 2022)
COVID-19 pandemic happened 100 years after Spanish Flu which caused high mortality in the world. It raised awareness about the importance to have drug development strategy acceleration. One of the drug development methods is drug repurposing. The urge for a deeper review of this method will be discussed in this article. The research method was reviewer literature that describes the terminology, the use of drug repurposing in cancer, COVID-19 and other diseases therapies and also the advantages to using drug repurposing method in drug development. The results showed some similar terms in drug repurposings such as drug repositioning, drug reprofiling, and drug rediscovery that makes drug repurposing preferred for old drug in new indication. Drug repurposing for anticancer are thiotepa, doxorubicine, gemcitabine, and raloxifene. Drug repurposing for COVID-19 are dexamethasone, methylprednisolone, sarilumab, heparine, enoxasaparine, rivaroxabane, and fondaparinux. The other uses are zidovudine, minoxidil, sildenafile, rituximab, and ketoconazole. The advantages from this method are higher time and cost-efficiency. Hesitance, drug therapy with drug repurposing method should be a priority for drug development nowadays.